Left atrial flow propagation velocity: a new approach for assessment of left atrial reservoir function - Palecek, Tomas; Lubanda, Jean-Claude; Trckova, Radka; Linhart, Ales (The international journal of cardiovascular imaging, 2011)
To assess the feasibility of left atrial flow propagation velocity (LAFPV) measurement and to evaluate the influence of preload alterations on this new parameter of left atrial (LA) reservoir function as compared to conventional echocardiographic indices. 30 healthy volunteers (26 ± 5 years, 20 males) underwent echocardiographic examination at rest, during passive leg lifting and after sublingual administration of nitroglycerine with subsequent Valsalva maneuver. LA reservoir function was assessed by conventional indices including LA expansion index, peak velocity and velocity-time integral of pulmonary venous systolic flow. As well, LAFPV was measured by color M-mode in an apical 4-chamber view as the slope of the transatrial flow wave during LA reservoir phase. LAFPV measurement was feasible in 25 subjects (83%). All conventional parameters of LA reservoir function were significantly altered from resting values by both load-modifying conditions. However, LAPFV was not significantly altered by such maneuvers (228 ± 28 cm s⁻¹ at rest vs. 238 ± 3 cm s⁻¹ during leg lifting, P = NS, vs. 218 ± 38 cm s(-1) after nitroglycerin with Valsalva maneuver, P = NS vs. rest, P < 0.01 vs. leg lifting). LAFPV can be measured in a majority of subjects and represents a new, less load-dependent index of LA reservoir function that may more appropriately reflect LA compliance.
Keywords: Muscle Contraction; Reproducibility of Results; Pulmonary Veins; Compliance; Valsalvův manévr; reprodukovatelnost výsledků; Heart Atria; Analysis of Variance; Blood Flow Velocity; Valsalva Maneuver; Predictive Value of Tests; Nitroglycerin; odchylka pozorovatele; svalová kontrakce; mužské pohlaví; Atrial Function, Left; prediktivní hodnota testů; Adult; mladý dospělý; analýza rozptylu; studie proveditelnosti; Echocardiography, Doppler, Color; srdeční síně; barevná dopplerovská echokardiografie; Young Adult; pulzní dopplerovská echokardiografie; ženské pohlaví; Humans; nitroglycerin; Echocardiography, Doppler, Pulsed; Hemodynamics; venae pulmonales; hemodynamika; vazodilatancia; Vasodilator Agents; srdce - funkce levé síně; dospělí; rychlost toku krve; poddajnost; Female; Observer Variation; Feasibility Studies; lidé; Male